Obligations, precautions and pending issues in regulatory development for radiopharmaceuticals in Brazil - Maryelle Moreira Lima Gamboa; Heveline Rayane Moura Roesch; Vanessa Pinheiro Amaral Lemos; Bruna Oliveira Rocha; Ralph Santos-Oliveira (Universidade de São Paulo, 2014)
Radiopharmaceuticals are compounds that have a radionuclide and may be gamma-radiation emitter (γ) or positrons emitter (β+), linked to a molecule with specific diagnostic and therapeutic purposes. The progress in the use of radiopharmaceuticals has culminated to a sector in common with other types of drugs: regulation and surveillance. From 2006 on, production, marketing and use of these drugs were open to the Brazilian market granting much more freedom due to the Constitutional Amendment 49, resulting from the previous Constitutional Amendment 199/03 which removes the Union monopoly for this kind of manipulation and granted this production to other nuclear medicine. From this date on, the amount of this type of sold product have been greatly increased, and the nucleus of surveillance and regulation in Brazil have also advanced in the legislative processes, creating documents that are now more focused on radiopharmaceuticals in the national territory (Resolutions No. 63 and No. 64). In international overview, there is too much to be done in regulatory terms in Brazil, such as adding mainly issues of drugs surveillance to pharmacovigilance practice in radiopharmaceuticals drugs.